2011
DOI: 10.1111/j.1462-2920.2011.02588.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of the Yersinia pseudotuberculosis complex according to multilocus sequence typing

Abstract: SummaryMultilocus sequence analysis of 417 strains of Yersinia pseudotuberculosis revealed that it is a complex of four populations, three of which have been previously assigned species status [Y. pseudotuberculosis sensu stricto (s.s.), Yersinia pestis and Yersinia similis] and a fourth population, which we refer to as the Korean group, which may be in the process of speciation. We detected clear signs of recombination within Y. pseudotuberculosis s.s. as well as imports from Y. similis and the Korean group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
90
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 64 publications
0
90
2
3
Order By: Relevance
“…According to this interpretation, the Y. pestis genealogy is rooted by Y. pseudotuberculosis at the base of branch 0, and SNPs have accumulated serially along branch 0 and subsequently along branches 1 and 2. All Y. pestis isolates, including the genomes analyzed here, cluster within one multilocus sequence type that is embedded within the Y. pseudotuberculosis population structure (20). These observations show that Y. pestis is a genetically monomorphic clone of Y. pseudotuberculosis, which has greater diversity.…”
Section: Resultsmentioning
confidence: 66%
“…According to this interpretation, the Y. pestis genealogy is rooted by Y. pseudotuberculosis at the base of branch 0, and SNPs have accumulated serially along branch 0 and subsequently along branches 1 and 2. All Y. pestis isolates, including the genomes analyzed here, cluster within one multilocus sequence type that is embedded within the Y. pseudotuberculosis population structure (20). These observations show that Y. pestis is a genetically monomorphic clone of Y. pseudotuberculosis, which has greater diversity.…”
Section: Resultsmentioning
confidence: 66%
“…The Y. pseudotuberculosis O:1a strains isolated in Brazil were clustered in the largest population group defined by an MLST-based population structure study (Laukkanen-Ninios et al, 2011). In addition, the Y. pseudotuberculosis O:1a strains deposited in the Y. pseudotuberculosis MLST database were typed into seven STs (9, 12, 16, 42, 43, 85, and 86) and have also been isolated worldwide from human and nonhuman sources (Fredriksson-Ahomaa, 2007;Laukkanen-Ninios et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In a global analysis of all Y. pseudotuberculosis strains listed in the Y. pseudotuberculosis MLST database including the strains of this study, it was observed that the Y. pseudotuberculosis O:3 strains were distributed into 17 different STs (3,4,14,19,25,30,32,43,50,57,58,59,60,61,62,63,and 64). These strains were isolated globally from human and nonhuman sources and are described as having low pathogenic potential (Fukushima et al, 2001;Fredriksson-Ahomaa, 2007;Laukkanen-Ninios et al, 2011). Despite the low pathogenicity characteristic of Y. pseudotuberculosis O:3 strains isolated around the world, some Y. pseudotuberculosis O:3 strains isolated in Brazil were responsible for severe and sometimes fatal diarrhea in cattle (Warth et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations